The Translation of Indonesian Cultural Lexicons in the Novel Saman - Evert H. Hilman (Bina Nusantara University, 2015)
Article was aimed to explore and identity the manners used by the translator in translating the Indonesian cultural lexicon in the novel Saman into English, and to find out which manners that contained the least semantic shifts concerning the problems of meaning related to cultural differences. Method applied was descriptive qualitative research by collecting and analyzing both the Indonesian and English versions of the novel. The samples were classified by Newmark four categories: loan words, cultural equivalent, functional equivalent, and addition. It can be concluded that there are only seven manners found from the collected data but only four manners used in the analysis, they are loan word, cultural equivalent, functional equivalent, and addition.